Staging supernatural creatures in a computer-based visualisation of London's sixteenth-century Rose Theatre. Issue 1 (2nd January 2017) - Tompkins, Joanne; Kastanis, Lazaros
ABSTRACT: This paper argues for recreating performance techniques from early modern theatre by deploying a computer-based visualisation of the Rose Theatre, a London venue from the 1590s. It focuses on one spectacular performance feature in early modern theatre, the dragon, which communicated a combination of excitement, fear, and dread. This era marked a transition between the end of both pagan beliefs and an unquestioned acceptance of Christianity, and a more human-centred (and inquisitive) moment in early modern thinking. Yet the effect of such creatures does not disappear instantly: they continued to yield a fearful awe. Theatrically, this time was extremely dynamic in form and topic, but little is known about the detail of actual performative techniques used at the time. Dragons were known to have been staged at the Rose, as documented by the theatre's owner, but no detail on its size or the manner of its 'performance' remains. To illustrate the potential of digital visualisations for theatre generally and to explore how this dragon may have worked in a detailed virtual model of the Rose Theatre, we track practicalities of size and manoeuvrability; venue questions regarding scale; and theatrical matters of visual impact and effect.